P1180EVOLUTION OF SERUM B2MICROGLOBULIN LEVELS IN INCIDENT PERITONEAL DIALYSIS PATIENTS. (6th June 2020) - Barbieri, Diego; DELGADO, ANDRÉS FELIPE; García-Prieto, Ana; Vega, Almudena; Abad Esttebanez, Soraya; Muñoz de Morales, Alejandra; Carbayo, Javier; González-Rojas, Ángela; Acosta Barrios, Adriana; Goicoechea, Marian
Abstract: Background and Aims: Retention of ß2microglobulin (ß2M), an uremic toxin in the middle molecular range, has been associated with cardiovascular morbidity and mortality in dialysis patients. Although ß2M levels are usually measured in hemodialysis patients, this practice is not common among peritoneal dialysis (PD) patients. The aim of this study is to evaluate the evolution of serum ß2M levels in incident PD patients. Method: Prospective, observational study including incident PD patients in our hospital from January 2015 to October 2019. Patients with cardiorrenal syndrome or patients coming from hemodialysis were excluded. Serum ß2M levels were collected before starting PD and during follow up. Weekly KtV, residual renal function and cardiovascular events were also collected during follow up. Results: We included 30 patients with a mean age of 57 +/- 17 years. 56.3% were male and 15.6% were diabetic. Mean follow up was 19.8 +/- 16.9 months. 18 patients were on continous ambulatory PD and 12 in automated PD. Mean serum ß2M levels before starting PD were 12.8 +/- 6.6 mg/l and they remained stable during follow up (12.9 +/- 5.2 mg/l, 15 +/- 4.2 mg/l, 14.3 +/- 6.9 mg/l, 10.2+/- 4.5 mg/l at month 6, 12, 24 and 36, respectively; p NS). No differences in serum ß2M levels were observed between continous ambulatory PD and automated PD. Serum ß2M levels were inversely and significantly correlated with weekly KtV (r= -0.943; p 0.009) and residual renal function (r= -0.829; p 0.042). One cardiovascular event was recorded during follow up. Conclusion: Serum ß2M levels remain stable during follow up in our cohort of incident PD patients and is significantly and inversely correlated with weekly KtV and residual renal function. Serum ß2M levels monitoring could be helpful in these patients and would yield important information in this population.